“Fora do Eixo: Estado ou mercado?” Modos de mediação entre produção cultural, política e mercado no Brasil - Victoria Irisarri (Ciências Sociais Unisinos)
Forms of contemporary cultural production in Brazil have articulated emerging social forms that put strain and open new questions on the boundaries between cultural production, the political and the market. This paper seeks to analyze the relationships between cul- tural production, the market and the political produced by an emerging artistic-cultural movement, Fora do Eixo. This movement emerged in the last decade, and is characterized by its organization in an articulated collective network and the use of digital technologies for work on cultural production. Drawing upon ethnographic work, this paper analyses some of the meanings that Fora do Eixo gives to certain actions of cultural production, transcending the analytical simplifications to understand the modes of mediation among culture, politics and the market that these movements produce in their own terms.